2006
DOI: 10.1128/iai.01660-05
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity ofMycobacterium tuberculosisAntigens inMycobacterium bovisBCG-Vaccinated andM. bovis-Infected Cattle

Abstract: The development of novel vaccine strategies supplementing Mycobacterium bovis BCG (BCG) constitutes an urgent research challenge. To identify potential subunit vaccine candidates, we have tested a series of eight recently identified Mycobacterium tuberculosis antigens in M. bovis-infected and BCG-vaccinated cattle. These antigens were characterized on the basis of their ability to induce in vitro gamma interferon responses in infected or BCG-vaccinated calves. We were able to establish a hierarchy of these ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…The specific protein and nonprotein Ags used in this study were .98% pure and were tested for endotoxin levels using the ToxinSensor Chromogenic LAL Endotoxin Assay Kit (GenScript). Levels of endotoxin were ,3 endotoxin U/mg, a concentration similar to that found in mycobacterial Ags used in other studies (47).…”
Section: Abs and Reagentssupporting
confidence: 82%
“…The specific protein and nonprotein Ags used in this study were .98% pure and were tested for endotoxin levels using the ToxinSensor Chromogenic LAL Endotoxin Assay Kit (GenScript). Levels of endotoxin were ,3 endotoxin U/mg, a concentration similar to that found in mycobacterial Ags used in other studies (47).…”
Section: Abs and Reagentssupporting
confidence: 82%
“…14 These proteins are attractive targets because they are potent T cell antigens that encode several immunodominant molecules, which are strongly recognized by the immune systems in both animals and humans. 12,13,15 These are small, secreted antigenic proteins that have been demonstrated to likely be required for the growth and pathogenicity of Mtb. 12 A few of the esx members are deleted in BCG, which has been associated with its attenuation and therefore, its low efficacy, 12 which also suggests they may represent important immune targets to alter pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…High-density transposon mutagenesis screening suggests that neither of these genes is essential for in vitro growth or in vivo survival (55,56). However, it has been demonstrated that the proteins encoded by these genes are expressed and recognized in M. tuberculosis-infected and M. bovis-infected hosts, suggesting that they do play a role during infection (22,40). Of particular note, PPE18 (also known as Mtb39A and Rv1196) was identified by serological expression screening (22) and is undergoing evaluation as part of the promising polyprotein vaccine candidate Mtb72f (http://clinicaltrials.gov/ct2 /show/NCT00600782) (58,64).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Although not predicted to be essential (55,56), a number of reports indicate that PE13 and PPE18 are expressed and recognized during infection (22,40). Furthermore, PPE18 constitutes part of the polyprotein vaccine candidate, Mtb72f (58).…”
Section: Identification Of Rv0485mentioning
confidence: 99%